THE EFFECTIVENESS OF USING WORD MAPPING TECHNIQUE TO INCREASE STUDENT VOCABULARY - Humaira Humaira (Muhammadiyah University of Mataram, 2015)
This study aims to investigate about the Effectiveness of Using Word Mapping Technique in Teaching Students Vocabulary at The First Grade Students of SMAN 8 Mataram in Academic Year 2014/2015. There were 79 students as sample. This study used quasi experimental non-equivalent research design. The data analysis showed the mean score of experimental group is higher than the mean score of control group. the use of word mapping technique is effective in teaching vocabulary. The deviation of the two mean scores (26.78/17.2) was also significant. It read that the value of t-test was 4.35 while the value of t-table was 2.000 on the level of significant 0.05 (95%) and 2.660 on the level significant 0.01 (99%). This figure indicated that the value of t-calculated was higher than t-value of t- table 4.35 > 2.000 and 2.660. The data indicated that t-test was higher than t-table, it means that the alternative hypothesis (H3) is accepted. Word maps technique maintain the students learning about words through mapping because helps them examine the characteristics of the word concepts, categorize words, and see relationships among words that are similar as well as those that may be different.